Transforming Global Health Communications During the COVID-19 Pandemic: International Partner Perspectives - Mitra Sadigh; Swapnil Parve; Jamidah Nakato; Hamidah Babirye Nsereko; Majid Sadigh (Ubiquity Press, 2022)
Background: With the COVID-19 pandemic restricting travel, global health programs are faced with the challenge of bidirectionally supporting students, partners, and communities in new ways. Though other global health programs have-to the best of our knowledge-temporarily frozen, we at the Nuvance Health/University of Vermont Larner College of Medicine Global Health Program have carried forward by transforming our communications through launching a COVID-19 Resources Page with bi-weekly article summaries, redirecting our monthly eMagazine and weekly blog to pandemic themes, and staying in constant communication with our partners around the world. Objective: To investigate the extent to which our program's published content shifted in sync with the COVID-19 pandemic, as well as our international partners' perception of the COVID-19 resource center, eMagazine, and blog in terms of relevance, representation, and utility. Methods: A survey consisting of quantitative questions and open-ended response questions was allocated along the following themes: (1) eMagazine; (2) Global Health Diaries blog; (3) COVID-19 Resource Center including article summaries; and (4) communications. It was sent to 34 leaders in our partner sites across nine countries-Botswana, China, the Dominican Republic, India, Thailand, Russia, Uganda, Vietnam, and Zimbabwe-and filled out by 31. Findings: Survey results revealed overwhelmingly positive feedback from our global health partners who reported frequently using our COVID-19 resources, often as first-line information about the pandemic; feeling emotional support through our communications; enjoying content in our eMagazine and blog; and finding fair representation in our published content. Our global health program is more deeply connected than ever. Conclusions: Though global health programs seemingly have their hands tied, we are only beginning to imagine the breadth of new avenues for connectivity, learning, and sharing. We must all be creative about staying connected. There are avenues for global health advocacy yet to be discovered.